1985
DOI: 10.1111/j.1365-2362.1985.tb00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Total and unbound Cortisol‐, progesterone‐, oestrone‐ and transcortin‐binding activities in sera from patients with myocardial infarction: evidence for differential responses of good and bad prognostic cases

Abstract: Day-of-admission sera from myocardial infarction patients (MI) and patients with cardiopathies other than MI (non-MI) were analysed for total and unbound cortisol (F), progesterone (P4), oestrone (E1), and corticosteroid binding activities (CBG). The MI who survived (n = 28) showed high increases of F, P4 and E1 compared to healthy controls. By contrast, the MI who died within 10 days of admission (n = 6) had unchanged F and less increased P4 and E1 than survivors. The non-MI (n = 6) had higher F and E1 than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…108 The production of cortisol in adrenocortical cells in response to ACTH occurs within minutes, and there is a shift towards an increase in glucocorticoid and away from mineralocorticoid and androgen production. 113 The CBG concentration in serum and the CBG binding affinity are both decreased 22,23,26,238 resulting in a dramatic increase in the biological active free cortisol concentration. In addition, the glucocorticoid receptor shows an increased affinity to free hormone during the acute phase of critical illness.…”
Section: Hpa (Dys)function In Human Sepsismentioning
confidence: 99%
See 2 more Smart Citations
“…108 The production of cortisol in adrenocortical cells in response to ACTH occurs within minutes, and there is a shift towards an increase in glucocorticoid and away from mineralocorticoid and androgen production. 113 The CBG concentration in serum and the CBG binding affinity are both decreased 22,23,26,238 resulting in a dramatic increase in the biological active free cortisol concentration. In addition, the glucocorticoid receptor shows an increased affinity to free hormone during the acute phase of critical illness.…”
Section: Hpa (Dys)function In Human Sepsismentioning
confidence: 99%
“…18 Under basal conditions, 90-95% of plasma cortisol is bound to CBG, and it is generally believed that the fraction of CBG-bound cortisol has a limited access to target cells and, therefore, is biologically inactive. 19 CBG is a 'negative acute phase protein' and levels of CBG are reduced during stress, 20,21 inflammation 22,23 or infection/sepsis. [23][24][25][26] It has been proposed that during inflammation CBG is reduced through interactions of the steroid-bound CBG complex with serine proteases that are released by activated neutrophils.…”
Section: The Hpa Axismentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of just 34 patients also reported a negative association between cortisol concentration and risk of death (4). By contrast, three small studies of between 22 and 70 patients with few deaths suggested increased risk of death among patients with high cortisol concentrations (5-7).…”
Section: Discussionmentioning
confidence: 93%
“…The HLE cleavage of CBG results in a ten-fold decrease in its binding affinity 21 , thus releasing cortisol 10 . In states of stress such as sepsis 22 , burns 23 and myocardial infarction 24 , the free cortisol percentage increases to up to 20%, due to the saturation of available CBG by increased cortisol and reduced CBG levels (a result of increased CBG cleavage/catabolism and inhibited synthesis) 25,26 . Inflammatory cytokines such as IL-6, glucocorticoids, insulin, hyperthyroidism, nephrotic syndrome, and cirrhosis can also reduce CBG concentrations.…”
mentioning
confidence: 99%